Land‐use intensification increases richness of native and exotic herbaceous plants, but not endemics, in Malagasy vanilla landscapes. Issue 5 (22nd February 2021) - Raveloaritiana, Estelle; Wurz, Annemarie; Grass, Ingo; Osen, Kristina; Soazafy, Marie Rolande; Martin, Dominic A.; Faliniaina, Lucien; Rakotomalala, Nantenaina H.; Vorontsova, Maria S.; Tscharntke, Teja; Rakouth, Bakolimalala
Abstract: Aim: North‐eastern Madagascar is a hotspot of plant diversity, but vanilla and rice farming are driving land‐use change, including slash‐and‐burn management. It still remains unknown how land‐use change and land‐use history affect richness and composition of endemic, native and exotic herbaceous plant species. Location: North‐eastern Madagascar. Methods: We assessed herbaceous plants along a land‐use intensification gradient ranging from unburned land‐use types (i.e. old‐growth forest, forest fragment and forest‐derived vanilla agroforest) to burned land‐use types (i.e. fallow‐derived vanilla agroforest, woody fallow and herbaceous fallow) and rice paddy. We compared land‐use types and analysed the effects of land‐use history, canopy closure and landscape forest cover on species richness. Additionally, we analysed species compositional changes across land‐use types. Results: Across 80 plots, we found 355 plant species (180 native non‐endemics, 57 exotics, 60 endemics and 58 species of unknown origin). Native and exotic species richness increased with increasing land‐use intensity, whereas endemics decreased. Unburned land‐use types had higher endemic species richness (4.28 ± 0.37 [mean ±  SE ]) than burned ones (2.4 ± 0.21). Exotic and native species richness, but not endemics, decreased with increasing canopy closure. Increasing landscape forest cover reduced exotic, but not native or endemic richness. Species composition of old‐growth forests was unique compared to all other land uses and forest‐derived, not fallow‐derived vanilla agroforests, had a similar endemic species composition to forest fragments. Main conclusions: Our results indicate that old‐growth forests and forest fragments are indispensable for maintaining endemic herbaceous plants. We further show that the land‐use history of agroforests should be considered in conservation policy. In forest‐derived vanilla agroforests, management incentives are needed to halt loss of canopy closure, thereby maintaining or even enhancing endemics. In conclusion, considering species origin (endemic, native and exotic) and composition is essential for the identification of suitable management practices to avoid irreversible species loss. Abstract : Expanding agriculture threatens forests and biodiversity in Madagascar. Here we focus on the response of little‐studied herbaceous plant diversity to land‐use change. We differentiated between endemic and non‐endemic species and compared their response to land‐use change. We show that while non‐endemic species richness is increasing under land‐use intensification, endemic species richness is decreasing. Only endemic species richness was shaped by land‐use history, with higher richness and different species composition on unburned land compared to burned land.